Removal of Artificial Rhodamine B Synthetic Dye Waste Using Magnetic Nanoparticle Adsorbents - Irwan, Irwan; Mardani, Mardani; Sari, Husna; Safitri, Aida; Zaini, Halim (Politeknik Negeri Lhokseumawe, 2025)
The use of synthetic dyes as dyes is increasing so that the waste is polluting the environment. One of the dangerous wastes that damages the environment and causes health problems is rhodamine B dye. The removal of rhodamine B dye is carried out by adsorption using an adsorbent that has been modified to provide magnetic properties. The aim of the research is to synthesize magnetic adsorbent nanoparticles using the co-precipitation method and use them to reduce the concentration of rhodamine B dye in artificial wastewater at various time variations. The study shows that magnetic nanoparticle adsorbents were successfully synthesized using the precipitation method. The adsorbent particles provide a magnetic effect on external magnetic forces, which shows that the adsorbent nanoparticles are magnetic. The application of magnetic adsorbent nanoparticles showed that the longer the adsorption time, the percentage of rhodamine B dye removal increased. The highest removal was obtained at 86% at an adsorption time of 90 minutes and an adsorbent mass of 4 g.